Polymorphic Identification of Simple Sequence Repeat (SSR) Marker for Developing Aluminum-Tolerance Upland Rice - Yuliana Galih Dyan Anggraheni; Enung Sri Mulyaningsih; Dody Priadi; Puspita Deswina; Yuli Sulistyowati; Eko Binnaryo Mei Adi; Ambar Yuswi Perdani; Fiqolbi Nuro; Yashanti Berlinda Paradisa (Jurnal Biodjati, 2020)
SSR marker is one of the genetic markers widely applied in plant breeding programs. The application of molecular markers in plant breeding is meant to accelerate the selection of cross-progeny. The research aimed to identify the SSR primers polymorphism between the parent and control that linked to Al tolerance and verify the cross-progeny of five crosses. The result gained from 37 SSR primers used in this study showed that only nine primers are polymorphic. These nine polymorphic primers are RM257, RM214, RM247, RM205, RM490, RM262, RM569, RM271, and RM19. The application of polymorphic markers on five cross-progeny which have shown the same band pattern as the parents and tolerant control on the use of 9 SSR primers recorded as follows: RM257 2 lines, RM214 5 lines, RM247 5 lines, RM205 lines, RM490 13 lines, RM262 5 lines, RM569 7 lines, RM271 4 lines, and RM19 6 lines. The selected SSR primers linked to Al tolerance in this research can be used as a reference for molecular breeding strategies to develop new Al tolerance rice varieties in dryland conditions.